Hydraulic and Separation Characteristics of an Industrial Gas Centrifuge Calculated with Neural Networks; AIP Conference Proceedings; Vol. 1938 : Isotopes: Technologies, Materials and Application (ITMA-2017) - Butov V. G. Vladimir Grigorievich; Timchenko S. N. Sergey Nikolaevich; Ushakov I. A. Ivan Alekseevich; Golovkov N. Nikita; Poberezhnikov A. D. Andrey Dmitrievich (2018, 2018)
Title screen